1999
DOI: 10.1177/002215549904700812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Immunolabeling Techniques on the Detection of Small-cell Lung Cancer Cells in Bone Marrow

Abstract: SUMMARY Recent reports have suggested that the immunodetection of tumor cells in bone marrow of small-cell lung cancer (SCLC) patients is by far more effective than traditional cytohistological methods and that this may be clinically relevant. This study aimed to evaluate whether the level of detection of tumor cells in bone marrow is affected by different immunostaining methods. Using two anti-NCAM monoclonal antibodies (MAbs), we compared four different "sandwich" methods on cytospin preparations of the N592… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The detection of the presence of epithelial cells in bone marrow has been studied as a prognostic factor in many epithelial malignancies such as breast (Braun et al, 2000), small- (Pasini et al, 1998;Pelosi et al, 1999a) and non small-cell lung cancer (Passlick et al, 1999) and oesophageal cancer (Thorban et al, 1996). Bone marrow isolated tumour cells are also evident in many patients with gastric cancer, but its prognostic significance is still uncertain (Funke and Schraut, 1998;Hermanek et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of the presence of epithelial cells in bone marrow has been studied as a prognostic factor in many epithelial malignancies such as breast (Braun et al, 2000), small- (Pasini et al, 1998;Pelosi et al, 1999a) and non small-cell lung cancer (Passlick et al, 1999) and oesophageal cancer (Thorban et al, 1996). Bone marrow isolated tumour cells are also evident in many patients with gastric cancer, but its prognostic significance is still uncertain (Funke and Schraut, 1998;Hermanek et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the samples and the immunocytochemical procedures were performed as previously described with some modifications (Pelosi et al, 1999a). Briefly, bone marrow aspirates (4 to 6 ml each) were collected in heparinized syringes, diluted with an equivalent volume of RPMI 1640 and sedimented onto a Ficoll-Hypaque density-gradient.…”
Section: Examination Of Bone Marrowmentioning
confidence: 99%
“…A first step in working with tissue‐specific markers is to select a protein and its antibody. Some that have already been tested include monoclonal antibodies against NCAM for detection of micrometastases in bone marrow aspirates of small‐cell lung cancer patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BMA from healthy volunteers and patients with unrelated, non-malignant diseases provided the control group for non-carcinoma patients. In a set of experiments we used BMA from healthy volunteers and from patients with unrelated, non-malignant diseases artificially contaminated with a known number of tumour cells at different dilutions in order to assess the sensitivity of our immunocytochemical method in the detection of NCAM-reactive tumour cells as described elsewhere (Pelosi et al, 1999). Results of these artificial contamination tests showed that NCAM-positive tumour cells were detected in expected quantities in all mixtures up to the final dilution of 1/10 5 bone marrow cells (data not shown).…”
Section: Immunocytochemical Proceduresmentioning
confidence: 99%
“…Results of these artificial contamination tests showed that NCAM-positive tumour cells were detected in expected quantities in all mixtures up to the final dilution of 1/10 5 bone marrow cells (data not shown). Double immunostains for NCAM and low molecular weight cytokeratins were carried out in both BMA and artificial mixtures to differentiate, in doubtful cases, true tumour epithelial cells from other NCAM-positive non-tumour cells, including natural killer (NK) cells, as described elsewhere (Pelosi et al, 1999).…”
Section: Immunocytochemical Proceduresmentioning
confidence: 99%